1999
DOI: 10.1007/s101520050024
|View full text |Cite
|
Sign up to set email alerts
|

The use of fish metabolic, pathological and parasitological indices in pollution monitoring

Abstract: The complex interactions between parasites, hosts and the environment are influenced by the stability of the ecosystem. Heteroxenous parasites, with complex, multiple-host life cycles, can persist only in habitats where the full range of their required hosts are present. Conversely, in impoverished environments such as those impacted by environmental stress, monoxenous species that have simple, single-host life cycles are likely to predominate. In the present study, we analyzed the ratio between heteroxenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 43 publications
0
49
0
1
Order By: Relevance
“…We presume that these two parasites have been carried into the Mediterranean on their Erythrean immigrant hosts. Co-invasion of the fish and their parasites has previously been reported for parasitic copepods, gill parasitic monogeneans and for endoparasitic digeneans on fish hosts (Fischthal, 1980;Diamant et al, 1999;Pasternak et al, 2007;ElRashidy and Boxshall, 2010;. In addition to coinvasion of parasites and their hosts, the phenomenon of host switching of some parasitic copepods was reported by El-Rashidy and Boxshall (2010 …”
Section: Introductionmentioning
confidence: 80%
“…We presume that these two parasites have been carried into the Mediterranean on their Erythrean immigrant hosts. Co-invasion of the fish and their parasites has previously been reported for parasitic copepods, gill parasitic monogeneans and for endoparasitic digeneans on fish hosts (Fischthal, 1980;Diamant et al, 1999;Pasternak et al, 2007;ElRashidy and Boxshall, 2010;. In addition to coinvasion of parasites and their hosts, the phenomenon of host switching of some parasitic copepods was reported by El-Rashidy and Boxshall (2010 …”
Section: Introductionmentioning
confidence: 80%
“…Generally, infections with ectoparasites tend to increase, whereas infections with endoparasitic helminths tend to decrease with increasing levels of pollution (Sures, 2005). Differences in the susceptibility of heteroxenous and monoxenous parasites can be used to indicate environmental pollution by calculating the ratio of the sums of heteroxenous and monoxenous (H/M) parasite individuals per host, as well as the ratio of heteroxenous and monoxenous parasite species richness found on the host fish (S H /S M ) as suggested by Diamant et al (1999). The authors found higher H/M ratios and higher S H /S M species richness ratios when comparing parasite communities of rabbitfish (Siganus rivulatus) sampled from an ecologically stable habitat of the Red Sea as compared with the community of fish sampled from anthropogenically impacted environments.…”
Section: Effects Of Pollutants On Parasite Abundancementioning
confidence: 99%
“…Fish parasites have been used as biological and environmental indicators (for a review see Palm, 2011), especially for environmental change and pollution (Diamant et al, 1999;Dzikowski et al, 2003;Palm & R眉 ckert, 2009) or environmental stress (Landsberg et al, 1998). Sures (2001Sures ( , 2003 used acanthocephalan parasites to detect heavy metal pollution, because acanthocephalans accumulate 1000 times higher amounts of heavy metals in contrast to their host tissues.…”
Section: Introductionmentioning
confidence: 99%